2021
DOI: 10.1021/acs.analchem.1c04268
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Tendencies of Substances Used as Calibrants for Quantitative Nuclear Magnetic Resonance Spectroscopy

Abstract: Atmospheric moisture can contaminate calibrants for quantitative nuclear magnetic resonance (qNMR) spectroscopy and cause systematic errors in qNMR measurements. Therefore, coulometric Karl Fischer (CKF) titration was used to evaluate the hygroscopic tendencies of several organic compounds that are commonly used as calibrants for qNMR spectroscopy: benzoic acid, dimethyl sulfone, 1,3,5-trimethoxybenzene, acetanilide, dimethyl terephthalate, and 1,2,4,5-tetramethylbenzene. Samples were placed in a sealed humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that dimethylsulfone reagents absorb 7.5% moisture after opening a reagent bottle at 22 °C and 100% humidity. 29 Using this coaxial-tube qNMR method, 8.3% hydration was confirmed in dimethylsulfone. Similar hygroscopicity has also been reported for amino acids 30 and pantothenic acids.…”
Section: Tmentioning
confidence: 99%
“…Previous studies have indicated that dimethylsulfone reagents absorb 7.5% moisture after opening a reagent bottle at 22 °C and 100% humidity. 29 Using this coaxial-tube qNMR method, 8.3% hydration was confirmed in dimethylsulfone. Similar hygroscopicity has also been reported for amino acids 30 and pantothenic acids.…”
Section: Tmentioning
confidence: 99%
“…6 However, the presence of moisture in DMS and other reference materials represents a problem that can make their quantitative determinations less accurate. 7 Water represents the only material whose purity is not affected by the presence of moisture. It is also readily available.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl sulfone (DMS) has been proposed as the universal reference material 6 . However, the presence of moisture in DMS and other reference materials represents a problem that can make their quantitative determinations less accurate 7 …”
Section: Introductionmentioning
confidence: 99%
“…Around thirty related articles were referenced as an indication of the usefulness of the constant-current coulometry. In the last six years, some articles based on the use of coulometry, from the analytical point of view, were published describing the application to the detection and quantification of a variety of compounds from metals, pharmaceuticals, water, antioxidants, gases, and certified materials [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Furthermore, numerous papers on coulometry have been published in education journals due to their instructional character (see recent papers on coulometry for chemical education [ 19 , 20 , 21 ] and the references therein).…”
Section: Introductionmentioning
confidence: 99%